Siyasi gelişme ve laiklik anlayışındaki değişim : AK Parti dönemi - Sağdıç, Esma (My University, 2024)
Bu çalışma, Türk siyasi hayatındaki laiklik kavramını Türk demokrasisi, insan hakları ve birey-devlet ilişkileri üzerindeki etkisini inceleyerek tarihsel kurumsalcılık perspektifinden geçmişten günümüze olan etkisini tartışmayı amaçlamaktadır. Buradan hareketle Türk siyasetinde laiklik meselesinin hangi olgularla açıklanabileceğine dair bir bakış açısı sunmayı hedeflemektedir. Siyasi gelişme açısından önemli adımların atılmaya başlandığı ve Avrupa Birliği’ne giriş süreciyle siyasi, toplumsal ve ekonomik alanda reformların yapıldığı AK Parti dönemi bu çalışmada yakın plana alınmıştır. Çalışmada, nitel araştırma yöntemlerinden betimsel analiz metodu kullanılmıştır. “AK Parti döneminde siyasal gelişme ve laikliğin kurumsallaşması ne şekilde olmuştur?” araştırma sorusu ise tezin genel çerçevesini oluşturmaktadır. Çalışmada ulaşılan başlıca sonuçlar, siyasi gelişme arttıkça laikliğin pasifleştiği ve demokrasi kurumsallaştıkça Türk siyasi hayatında bir mesele olarak görülen pek çok konunun çözülebileceği görüşüdür. Türkiye’de uzun bir süre katı bir laiklik anlayışının hakim olması demokrasinin yeterince siyasi kültüre yerleşememesi ile açıklanabilir. Bu bağlamda demokrasi kültürü yerleştikçe, eşitlik anlayışı geliştikçe siyasi gelişme kriterlerinin de gelişeceği öngörülebilmektedir.

This study examines the concept of secularism in Turkish political life, Turkish democracy, human rights and individual-state relations. From the past to the present from the perspective of historical institutionalism by examining its impact on aims to discuss. From this point of view, with what facts is the issue of secularism in Turkish politics? It aims to offer a perspective on how it can be explained. Important steps in terms of political development reforms in the political, social and economic fields began to take place and with the process of accession to the European Union.The AK Party period in which it was built is taken into close focus in this study. In the study, qualitative research methods. Descriptive analysis method was used. “What happened to the political development and institutionalization of secularism during the AK Party period? “How did it happen?” The research question constitutes the general framework of the thesis. The main findings were reached in the study.The results show that, as political development increases, secularism becomes passive and democracy becomes institutionalized, leading to a decline in Turkish political life. It is the view that many issues that are seen as problems can be solved. Strict secularism has existed in Turkey for a long time. The dominance of this understanding can be explained by the fact that democracy has not sufficiently settled into the political culture. In this context as the culture of democracy becomes established and the understanding of equality develops, political development criteria will also improve can be predicted.
Political development and change in the understanding of secularism : AK Party period
Keywords: 1980-; Adalet ve Kalkınma Partisi (Türkiye); AK Parti Dönemi; AK Party Era; Democracy; Demokrasi; Historical Institutionalism; Laiklik; Political Development; Politics and government; Secularism; Siyaset ve yönetim; Siyasi Gelişme; Tarihsel Kurumsalcılık; Türkiye